Невідомий польський документ про Великий голод в Україні: зі спогадів керівника радянського відділу східного департаменту МЗС II Речіпосполитої Станіслава Забелла - Кушнеж, Р. (Український історичний журнал, 2020)
Мета дослідження – оприлюднити та проаналізувати досі невідомий фраґмент спогадів польського дипломата про Великий голод в Україні 1932–1933 рр. Методологія полягає у застосуванні критичного аналізу до джерела, порівнянні його змісту з іншими доступними джерелами дипломатичного та розвідувального походження. Наукова новизна. Уперше опубліковано і проаналізовано невідомі раніше матеріали про Голодомор 1932–1933 рр. авторства провідного радянолога МЗС міжвоєнної Польщі. Висновки. Про Голодомор 1932–1933 рр. написано багато. Проводяться нові дослідження. Аспект Великого голоду також неодноразово аналізувався на підставі дипломатичної й розвідувальної документації II Речіпосполитої. Утім, це не означає, що в польських архівах уже не можна віднайти невідомих матеріалів. І хоч більшість документів опубліковано, однак досі трапляються цікаві знахідки. Одна з таких – фраґмент спогадів дипломата, котрий, перебуваючи в Москві, не тільки чув про голод і читав про нього в рапортах польських консульських установ з України, але й, заступаючи керівника ґенерального консульства Польщі у Харкові, у серпні та вересні 1933 р. особисто зіткнувся з реаліями голоду. С.Забелло аналізує причини трагедії селянства, на основі розмов зі впливовим радянським журналістом К.Радеком намагається відповісти на питання, скільки людей померло, пише про акти канібалізму. The research goal is to publish an unknown fragment of the memories of the Polish diplomat about the Great Famine in Ukraine in 1932–1933. The research methodology. Critical source analysis and comparison with other available materials of the Polish Ministry of Foreign Affairs and the military intelligence. Scientific novelty. The following text analyzes, for the first time, unknown memoirs of the Holodomor of 1932–1933, written by S.Zabiełło, who was considered to be a leading Sovietologist in the Polish Ministry of Foreign Affairs in the interwar period. Conclusions. Much has already been written about the Holodomor of 1932–1933 and new researches are being underway. The aspect of the Great Famine has also been raised several times based on Polish diplomatic, consular and military intelligence documents of the Second Republic of Poland. This does not mean that no materials can be found in the Polish archives, where the Great Famine in Ukraine of 1932–1933 is mentioned. Of course, it is hard to expect to discover of a vast array of new and unknown sources. Most of the representative materials of this provenance have already been published. However, one of such unknown documents is a fragment of memories written by S.Zabiełło, which we provide in this paper. S.Zabiełło not only heard about hunger while in Moscow. He saw hunger with his own eyes when replacing the head of the Polish consulate general in Kharkiv, J.Karszo-Siedlewski, at the turn of August and September 1933. The Polish diplomat’s analyses have treated the issue of the causes of the tragedy that had affected the peasants. Based on conversations with the Soviet dignitary, K.Radek, S.Zabiełło estimated the number of famine victims. He also wrote about acts of cannibalism etc.